Pengaruh Customer Satisfaction Terhadap Customer Loyalty Pada Produk Jahe Merah Lapas Khusus Gunung Sindur - Michael Dwi Putra; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
The aim of this article is to examine the effect of the customer satisfaction dimension on customer loyalty for the Merah Gunung Sindur product. This research is quantitative in nature from a study involving questionnaires distributed to 30 buyers from both cooperatives and re-sellers of Gunung Sindur red ginger. Research data were analyzed using SPSS 26, namely validity and reliability tests, normality tests, linearity tests, and simple linear regression tests. The key findings of this study reveal that respondents show an average of "agree" to buy at cooperatives and resellers, which is significant between the two variables, namely customer satisfaction and customer loyalty, which have a positive effect on the performance of customer satisfaction on customer loyalty. Therefore it is recommended that both the Gunung Sindur cooperative and the reseller must be able to maintain service and customer satisfaction given the significant relationship of the two variables. However, cooperatives and resellers must not ignore the problem of customer service